2006
DOI: 10.1038/sj.bjc.6603179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adeno-associated virus type 2 genome in cervical carcinoma

Abstract: Adeno-associated virus (AAV) can impair the replication of other viruses. Adeno-associated virus seroprevalences have been reported to be lower among women with cervical cancer. In-vitro, AAV can interfere with the production of human papillomavirus virions. Adeno-associated virus-2 DNA has also been detected in cervical cancer tissue, although not consistently. To evaluate the role of AAV infection in relation to invasive cervical cancer, we performed a nested case -control study within a retrospectively foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In this study, we used the AAV2 serotype to transfer sgRNAs into HeLa cells. Previous studies have shown the efficiency of this serotype for gene transfer into cervical cancer cells 22 , 23 .…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we used the AAV2 serotype to transfer sgRNAs into HeLa cells. Previous studies have shown the efficiency of this serotype for gene transfer into cervical cancer cells 22 , 23 .…”
Section: Discussionmentioning
confidence: 96%
“…A case control study in pregnant and non-pregnant women found that AAV infection have any impact on cervical intraepithelial neoplasia development [65]. Moreover, a retrospective case control study by Zheng et al (2006) found a low proportion of cervical cancer biopsies containing AAV genomes and no evidence that the presence of AAV in cervical smears of healthy women would be associated with a reduced risk of cervical cancer [66]. Finally, an Iranian study from 2017 detected a low proportion of cervical biopsies containing AAV genome (14.8% cervical cancer cases and 14% healthy controls) and no significant difference in correlation between HPV and cervical cancer in the presence or absence of AAV infection was found [67].…”
Section: Aav Infection and Cervical Cancermentioning
confidence: 99%
“…These data point out that HPV could indeed be an AAV helper virus and that AAV as such can be considered sexually transmissible. [ 66 ] 2006 Sweden Cases = 104 Matched control = 104 Cervical smear; cervical tissue At baseline, 2% of case-women and 3% of control-women were positive for AAV type 2 DNA. At the time of cancer diagnosis, 12% of case-women and 3% of matched control-women were positive for AAV DNA.…”
Section: Introductionmentioning
confidence: 99%
“…This will allow for better manipulation of AAV replication and, ultimately, should greatly boost rAAV production. Furthermore, while certain groups fail to see a correlation [7-9], the vast majority of epidemiologic, animal, and tissue culture studies strongly suggest that AAV inhibits the carcinogenesis process [10-29]. Moreover, there is a long history of AAV functioning as an autonomous parvovirus during specific circumstances.…”
Section: Introductionmentioning
confidence: 99%